Effect of high temperature stress during ripening on the accumulation of key storage compounds among Japanese highly palatable rice cultivars. (September 2020) - Ishimaru, Tsutomu; Miyazaki, Masayuki; Shigemitsu, Takanari; Nakata, Masaru; Kuroda, Masaharu; Kondo, Motohiko; Masumura, Takehiro
Abstract: High temperature stress during ripening increases the frequency of chalky grains, resulting in a lower market value for rice ( Oryza sativa L.). Changes in starch properties and the accumulation pattern of storage proteins are proposed to be related to the occurrence of chalky grains. This study investigated changes in the accumulation of key storage compounds in the grains of Japanese highly palatable rice cultivars, subjected to high temperature stress when grown in a growth chamber and the field. The 13 kDa prolamin content was significantly reduced in a highly heat-sensitive cultivar, Tsukushiroman, whereas the 13 kDa prolamin content was not affected in a heat-tolerant cultivar, Genkitsukushi, even in a high temperature chamber condition (31/26 °C day/night), when compared with the control chamber condition (26/21 °C day/night) for both genotypes. In addition, grains grown in field conditions revealed that severely chalky grains had less 13 kDa prolamin than perfect grains in all five genotypes. Changes in amylose content and the distribution of amylopectin chain lengths did not explain the difference in grain appearance both for chamber and field experiments. These results strongly suggest that physiological processes linked with the synthesis of 13 kDa prolamin are associated with grain appearance in Japanese highly palatable under high temperature stress. Highlights: Key storage compounds for grain appearance were evaluated in five rice cultivars. Amylose content and amylopectin chain length did not explain the visual differences. Chalky grains had less 13 kDa prolamin than perfect grains. Heat-induced grain chalkiness is linked to 13 kDa prolamin synthesis physiology.